Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1155/2011/201254
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant-Producing Lactobacilli: Screening, Production Profiles, and Effect of Medium Composition

Abstract: Biosurfactant production was screened in four lactobacilli strains. The highest biosurfactant production (excreted and cell-bound biosurfactants) was achieved withLactobacillus paracaseissp.paracaseiA20, a strain isolated from a Portuguese dairy plant, with a decrease in the surface tension of 6.4 mN m−1and 22.0 mN m−1, respectively. Biosurfactant production by this strain was evaluated under different culture broth compositions. The use of different nitrogen sources revealed that yeast extract is essential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 38 publications
(60 reference statements)
6
66
2
Order By: Relevance
“…Detailed studies on several mechanisms of interference of pathogen adherence and biosurfactant have been previously reported by several researchers . The mechanism of competitive exclusion has been demonstrated by quite a lot of Lactobacilli spp.…”
Section: Biosurfactant Producing Lactobacilli Sppmentioning
confidence: 99%
“…Detailed studies on several mechanisms of interference of pathogen adherence and biosurfactant have been previously reported by several researchers . The mechanism of competitive exclusion has been demonstrated by quite a lot of Lactobacilli spp.…”
Section: Biosurfactant Producing Lactobacilli Sppmentioning
confidence: 99%
“…Biosurfactants produced by bacteria can either be excreted or remain cell-bound. Gudiña et al [63] found that Lactobacillus coryniformis, Lactobacillus paracasei, L. plantarum and Leuconostoc mesenteroides produced cell-bound biosurfactants at higher levels than excreted ones. Cell-bound biosurfactant production has been observed in several species of Lactobacillus [64], including L. plantarum [65].…”
Section: Lactic Acid Bacteria Isolatesmentioning
confidence: 99%
“…The data is expressed as mean ± SD based on at least duplicate observations from three independent experiments. important factors influencing the cellular behaviors and the increase in pH value can lead to the inhibition of cell proliferation [45,46]. A colloidal dispersion of HAp microparticles at 10 mg/mL raised the pH of the culture media up to 7.76 and 7.97 (from 7.32) after 24 h and 1 wk of incubation at 37 C, respectively (Table.…”
Section: Cytotoxicity Of Rgo/hap Compositesmentioning
confidence: 99%